(2w-6)+4(-1-5w)=0

Simple and best practice solution for (2w-6)+4(-1-5w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2w-6)+4(-1-5w)=0 equation:


Simplifying
(2w + -6) + 4(-1 + -5w) = 0

Reorder the terms:
(-6 + 2w) + 4(-1 + -5w) = 0

Remove parenthesis around (-6 + 2w)
-6 + 2w + 4(-1 + -5w) = 0
-6 + 2w + (-1 * 4 + -5w * 4) = 0
-6 + 2w + (-4 + -20w) = 0

Reorder the terms:
-6 + -4 + 2w + -20w = 0

Combine like terms: -6 + -4 = -10
-10 + 2w + -20w = 0

Combine like terms: 2w + -20w = -18w
-10 + -18w = 0

Solving
-10 + -18w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -18w = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -18w = 0 + 10
-18w = 0 + 10

Combine like terms: 0 + 10 = 10
-18w = 10

Divide each side by '-18'.
w = -0.5555555556

Simplifying
w = -0.5555555556

See similar equations:

| 12+4x=5x | | y-4=-4(x+5) | | 6x-2=27 | | -3(2)-4y=4 | | (x-40)/40=1.5 | | 12n^2+16n^3=0 | | -14-13=55 | | 6y^2+31y+35= | | 50=601 | | t(n)=5+3(n-1) | | 2x=8sqrtx^2 | | 4(x+4)(x-5)=0 | | 3(2x-2)+11=4(x-3)-(2x+1) | | 5b-5-12b-4= | | y-4=-4[x+5] | | 3(4-3x)=2(2x+3) | | 3/5×3 | | 3x-5*(5/x) | | -4p+2(1-p)=2p-2(1-p) | | x+y+(2y+1)=40 | | 8p-1+5=-12 | | 4(2a+3)=(a-1)+31 | | 6x-5(-4x-5)=-1 | | X+4=8+2 | | 9x-(6x+5)=10 | | 2(x+1)=8-2(x-1) | | 8x+16y=24 | | 4-cos(2x)+5sin(x)=2sin^2(x)+5sin(x)+3 | | 3(8x-8)=24 | | (200/15)*20= | | 2(t-8)=4(2t-6) | | -2y+(-12)=y+3+2y |

Equations solver categories